2017
DOI: 10.3390/insects8020054
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biotic Factors Regulating Inter-Kingdom Engagement between Insects and Microbe Activity on Vertebrate Remains

Abstract: A number of abiotic and biotic factors are known to regulate arthropod attraction, colonization, and utilization of decomposing vertebrate remains. Such information is critical when assessing arthropod evidence associated with said remains in terms of forensic relevance. Interactions are not limited to just between the resource and arthropods. There is another biotic factor that has been historically overlooked; however, with the advent of high-throughput sequencing, and other molecular techniques, the curtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 150 publications
0
19
0
Order By: Relevance
“…Translocation is a process whereby microbes, many of which are commensals during life, move from the gastrointestinal tract to other regions of the remains . These microbes contribute significantly to decomposition (e.g., putrefaction) and can release volatile organic compounds that attract insects and scavengers . Recent postmortem microbiology has demonstrated that bacterial phyla Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria are regularly associated with decomposing remains regardless of carcass species, season, or soil type .…”
mentioning
confidence: 99%
“…Translocation is a process whereby microbes, many of which are commensals during life, move from the gastrointestinal tract to other regions of the remains . These microbes contribute significantly to decomposition (e.g., putrefaction) and can release volatile organic compounds that attract insects and scavengers . Recent postmortem microbiology has demonstrated that bacterial phyla Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria are regularly associated with decomposing remains regardless of carcass species, season, or soil type .…”
mentioning
confidence: 99%
“…Flies played an important role in transmitting foodborne pathogen. From the study of Jordan and Tomberlin (2017), it was found that, flies gave a higher prevalence of pathogens when compared to other collected samples from kitchen. Other than that, the hands of the worker are a great tool in transmitting pathogenic bacteria as well.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, the decomposition process happens faster in humid climates. Hence, a colder environment and lesser relative humidity will thwart microbial proliferation to a degree (Jordan and Tomberlin, 2017).…”
Section: Environmental and Population-based Diversitymentioning
confidence: 99%